2022
DOI: 10.3389/fped.2022.853517
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Abdominal Aortic Aneurysm: A Case Report and Literature Review

Abstract: Congenital abdominal aortic aneurysm is a rare disease with unknown etiology, and the common symptoms are abdominal pulsatile mass and pain caused by aneurysm rupture. The disease has a high mortality rate and fewer reports of surgical treatment. Here, we present a case of an idiopathic congenital abdominal aortic aneurysm. A 4-year-old boy had an abdominal pulsatile mass, and computed tomography angiography revealed an isolated infrarenal abdominal aortic aneurysm. To prevent rupture of the aneurysm, we repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Kidney failure or rupture-related mortality due to cAAA is 30.76%. 12 There is no universal approach to the management of cAAA. The timing of surgical treatment should be evaluated according to the size and location of the aneurysm, the presence of dissection and the risk of rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney failure or rupture-related mortality due to cAAA is 30.76%. 12 There is no universal approach to the management of cAAA. The timing of surgical treatment should be evaluated according to the size and location of the aneurysm, the presence of dissection and the risk of rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsatile abdominal mass and discomfort are typical signs of cAAA. Kidney failure or rupture‐related mortality due to cAAA is 30.76% 12 . There is no universal approach to the management of cAAA.…”
Section: Discussionmentioning
confidence: 99%
“…Only 32 cases have been reported recently, including our case. 3 ) A review 4 ) showed that males were almost twice as likely to develop congenital AAA than females, half of the patients were neonates and infants, and only 4 of 26 patients were diagnosed at over 3 years of age. Our patient was diagnosed later than normal.…”
Section: Discussionmentioning
confidence: 99%
“…Existem várias causas que levam a esse quadro como doença aterosclerótica, infecção, artrite e trauma. A maioria é assintomático e diagnosticado em exames de imagens ocasionais, sendo a complicação a ruptura desse aneurisma que leva uma severa hemorragia na intra-cavidade abdominal(ZHOU et al, 2022).…”
unclassified